x2-64x=0

Factor x out of x2.

x⋅x-64x=0

Factor x out of -64x.

x⋅x+x⋅-64=0

Factor x out of x⋅x+x⋅-64.

x(x-64)=0

x(x-64)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x=0

x-64=0

Set the first factor equal to 0.

x=0

Set the next factor equal to 0.

x-64=0

Add 64 to both sides of the equation.

x=64

x=64

The final solution is all the values that make x(x-64)=0 true.

x=0,64

Solve Using the Square Root Property x^2-64x=0